The Relationship between the Facilities and Infrastructure of the Balai Penyuluh Pertanian (BPP) KOSTRATANI and Its Function as a Data and Information Center at BPP Sidomulyo and Candipuro in South Lampung Regency - Safitri, Anggun; Listiana, Indah; Yanfika, Helvi; Silviyanti, Serly; Rangga, Kordiyana K. (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2023)
Agricultural Extension Service (Indonesian: Balai Penyuluh Pertanian; BPP) Strategic Command for Agricultural Development (Indonesian: Komando Strategis Pembangunan Pertanian; KOSTRATANI) serves as a crucial data and information center for agricultural extension activities. Through data collection, the BPP can provide extension workers with the necessary information to make informed decisions, create plans, and evaluate activities. As such, it is essential to support the role of BPP as a data and information center by providing adequate facilities and infrastructure. This study aims to examine the relationship between facilities and infrastructure and the function of BPP as a data and information center at BPP Sidomulyo and Candipuro in the South Lampung district. Data was collected in November 2021, and the study's respondents included 16 agricultural extension workers. The analysis was carried out using the Spearman rank statistic test, and the results revealed a positive relationship between facilities and infrastructure and the function of BPP KOSTRATANI as an information data center. The availability of facilities and infrastructure was found to be in the good to excellent category, with each percentage being 39.06 percent. These findings suggest the importance of supporting the BPP's facilities and infrastructure to maintain its role as a data and information center for agricultural extension activities.